Regional energy consumption policy practice to promote low-carbon economy - Sun, Xiaoting; Onuh, Willington O. (Frontiers in Environmental Science, 2024)
Energy is a fundamental driver of global economic and social development. However, the growth in CO2 emissions and the mounting environmental challenges are becoming increasingly problematic, placing constraints on the pace of economic advancement. To optimize the energy consumption structure and promote the development of low-carbon economy, this study takes Shaanxi Province as an example to analyze the influence of low-carbon economic policy variables on the energy consumption structure dominated by coal. The objective of this study is to examine the impact of policy variables on the evolution of energy consumption structures through the construction of a system dynamics model. Additionally, this study will investigate the policy optimization problem. The experimental results showed that the error of the simulation results was within ±10%, and the non-fossil energy consumption increased from 2.196,400 tons of standard coal in 2009 to 22.578 million tons in 2030, which was in line with the development trend. Under the four policy combinations, the share of coal will deduced to 57.8 percent in 2030. Moreover, the share of non-fossil energy would increase to 21 percent, and the share of natural gas would reach 16 percent. The research reveals that the proposed policy suggestions are of great significance to the optimization of the coal-dominated energy structure, and the model constructed can be effectively applied to the actual policy simulation and adjustment.